Intranest mutualisms between the forest fire ant Solenopsis virulens (Fr. Smith) (Hymenoptera; Formicidae) and two families of Hemiptera (Membracidae, Monophlebidae) in Brazilian Atlantic Forest - Pereira, Thalles Platiny Lavinscky; Bravo, Freddy; Delabie, Jacques Hubert Charles (EntomoBrasilis, 2021)
Hemipterans and ants are frequently recorded in trophobiotic associations, generally mutualism. Nests of the fire-ant Solenopsis virulens (Smith) found at the base of trees in the Atlantic Forest biome, Brazil, were investigated for their commensal fauna. The present study provides new information about the mutualism between the fire-ant with hemipterans Membracidae and Monophlebidae found in their nests, this report is the first mention of this kind of relationships in South America. Such associations are very common between ants and treehoppers but have seldom been reported with the family Monophlebidae.